Literacy resilience: bridging linguistic literacy and self-regulated learning for enhanced educational success - Amir, Alisa (Frontiers in Education, 2025)
This paper introduces the innovative concept of “literacy resilience (LR)” as a crucial link between linguistic literacy and self-regulated learning (SRL). The foundation of this concept rests on two fundamental assumptions. First, every educational interaction is a literate interaction, combining the skills of reading, writing, listening, and speaking. Second, self-regulated learning (SRL) is a multidimensional process, encompassing personal, behavioral, and environmental factors, enabling students to enhance their learning management. These principles led to the development of “literacy resilience.” This research aims to investigate “literacy resilience” as a critical connection between linguistic literacy and self-regulated learning, and explore teachers’ perceptions of its importance and their evaluation of students’ literacy resilience levels. The study surveyed 349 teachers across various fields using a dedicated questionnaire. Findings reveal a notable discrepancy between teachers’ perceptions of literacy resilience’s importance and their assessment of students’ levels. While teachers emphasize its high importance, they perceive students’ levels to be low, suggesting a gap between recognized importance and current development. Moreover, there is a significant lack of teachers’ knowledge of both literacy skills and SRL strategies. These findings highlight a potential discrepancy between teachers’ recognition of literacy resilience’s importance and students’ perceived competence, suggesting a need for targeted professional development initiatives.